SPECIFICITY OF THE ORIGIN AND ATTRIBUTION OF LACQUERED WORKS IN THE TECHNIQUE OF NAJEON CHILGI - Кузьміних, М. В. (Art and Design, 2023)
Purpose: identifying and establishing the difference between Korean, Chinese and Japanese techniques of lacquer art with inlay and summarizing these technical and technological features, which are related to historical and geographical frameworks in order to improve the process of attribution of Ukrainian works; Methodology. The method of systematization of information regarding the number of objects and their visual characteristics is applied. Methods of synthesis and generalization were used in the study of information and images regarding the origin of techniques, stages of creation of objects and their geographical framework for further comparison by visual characteristics with works in Ukrainian collections. Results. The peculiarities of Korean urushi lacquer techniques with mother-of-pearl inlay and provides information about existing works (Japanese, Chinese, namban, chinoiserie, japoneri) in Ukrainian museums and private collections. A study was conducted on the origin of Korean lacquer techniques and the history of their emergence. Analogues in terms of visual characteristics to lacquer works with inlay were found in Ukrainian collections. Scientific novelty. For the first time, the analysis of works in the traditional Korean technique of Najeon Chilgi was introduced into the scientific circulation of art history in Ukraine, the number of works in museum collections created using the urushi mother-of-pearl lacquer incrustation technique was determined, their origin was determined based on data provided by museums and thanks to the author's search for analogs, a comparison was made by visual characteristics of works from collections with similar works from foreign museums and collections. Practical significance. The presented material is a fragment in the process of researching Ukrainian collections of oriental urushi lacquer works, it supplements information about objects created in the Korean technique of Najeon Chilgi and provides information about urushi lacquer inlay techniques in Korea, their history and origin.